(untitled) (Research, Society and Development, 2020)
Nutritional knowledge can be characterized as a set of information acquired about food and nutrition through the skills of the cognitive process, or it is simply what is understood in relation to the general aspects of food. The aim of this research is to describe what scientific publications say about nutritional and supplemental knowledge among physical activity practitioners. This is a bibliographic review in which 16 scientific articles researched in the database SCIELO and Google Scholar in Portuguese were used between the years 2011 and 2019. The research participants are concerned with matters related to nutrition, however, there is little guidance, requiring a professional nutritionist together with the physical educator. Physical activity practitioners seek information from gym instructors, physical education teachers and also follow self-indication, which directly reflects in their conduct related to nutrition. It is concluded that, although most physical activity practitioners are interested in aspects of healthy eating, they have a moderate nutritional knowledge. There are erroneous practices and little knowledge in relation to dietary supplements, as well as the search for information and nutritional guidance with people not qualified for this purpose.